PENGARUH METODE PEMBELAJARAN DAN TIPE KEPRIBADIAN TERHADAP HASIL BELAJAR MATEMATIKA - Ismet, Ismet (AS-SALAM, 2015)
This study aimed to find out the effect of Role Playing Method macroand micro And Personality Type to a increase mathematic learningchievement.This research represent the quantitative research ofcomparability use the experiment method by desain.The result ofstudy shows: (1) the students achievement mathematic who studiedby macro role playing method was higher than those who studied bymicro role playing method, (2) the student who had exstrovert typestudied by macro role playing method had higher on mathematiclearning achievement than those who had extrovert type and studiedby micro role playing method, (3) the student who had introvert typeand studied by micro role playing method had higher on mathematiclearning achievement than those who introvert type and studiedmacro role playing method and (4) there was an interaction effectbetween the use of role playing method and personal type Someimplications of this study were: appliying role playing micro andmacro method in mathematics learning, should be considered thepersonal type (ekstrovert and introvert).Keywords: Role Playing, Personal Type, Learning MathematicAcievement.